The Crisis in British Army Recruiting in the 1930s - Hull, Chris (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1994)
AbstractDuring the 1930s, the British army suffered a shortage of recruits despite the depression. This study explores the response of the War Office to the crisis, which undermined the army's ability to undertake its peacetime and wartime roles. The study is important in helping to elucidate the army's place in society, as the War Office had to examine itself and its public image to understand the reasons for the shortage. The War Office concluded that its image as a bad employer, an inefficient military force and as the object of pacifist propaganda played a crucial role in deterring recruits. Despite intense, and partially successful, efforts to improve its public relations structure and measures to combat the bad image, the main reasons for the improvement in recruiting from the fall of 1937 were the lowering of the physical standards required of recruits and the improving conditions in the service. The army remained a source of public pride, but one that was separated from society and whose recruits tended to be attracted by economic incentives.